Produção de biomassa, teor e composição de óleo essencial de erva-baleeira (Varronia curassavica Jacq.) em diferentes níveis de adubação NPK - Mello, Romulo Marinho de (2020)
Black-sage belongs to the Boraginaceae family and it’s a native Brazilian plant. Its leaves synthesize essential oil rich in α-humulene, sesquiterpene to which the specie's anti-inflammatory power is conferred. Acheflan (Marca Registrada) phytomedicine was developed from its essential oil, which leveraged its economic importance. The study aimed to evaluate the field performance of black-sage plants submitted to different levels of fertilization in order to improve the biomass yield, content and essential oil quality. The experiment was conducted in the field, during the years 2019 and 2020. The treatments consisted of different doses of fertilization (half dose, one dose and two doses, in addition a control without fertilization). The initial calculation parameter for a dosewas: N -40 kg ha-¹; P2O5-43,75 kg ha-¹; K2O -22,5 kg ha-¹, in formulations of urea, super simple phosphate and potassium chloride. In addition, two different methods of extracting the essential oil were also tested: hydrodistillation and steam distillation. The following parameters were also analyzed: physiological (gas exchange and chlorophyll content); biometric production parameters (dry leaf weight, dry mass of branches, dry weight of aerial part, essential oil yield and essential oil content in relation to dry weight); quality parameters (concentration of the main essential oil compounds). The obtained results showed that the application of different fertilization doses in plants of black-sage did not present statistical difference on the production of dry biomass, however the use of two doses tends to produce more dry mass of leaves per area. For the first harvest, the essential oil content was higher in treatment without fertilization. There was no statistically significant difference on this variable for the second harvest. Different fertilizer doses in black-sage plants showed a statistical difference on the α-humulene content and the highest concentration obtained was with the application of one dose. In relation of other compounds, there was nostatistical difference. The main compounds obtained in the essential oil were α-humulene, α-pinene and α-santalene. The use of different fertilizer doses did not have a statistically significant influence on essential oil productivity. The high yield of essential oil for two doses fertilizer were due to the greater production of dry leaf mass per area, but without differing from the other treatments. There was no significant difference of yield in obtaining essential oil in different extraction methods.